2021
DOI: 10.1038/s41467-020-20255-4
|View full text |Cite
|
Sign up to set email alerts
|

A RAC-GEF network critical for early intestinal tumourigenesis

Abstract: RAC1 activity is critical for intestinal homeostasis, and is required for hyperproliferation driven by loss of the tumour suppressor gene Apc in the murine intestine. To avoid the impact of direct targeting upon homeostasis, we reasoned that indirect targeting of RAC1 via RAC-GEFs might be effective. Transcriptional profiling of Apc deficient intestinal tissue identified Vav3 and Tiam1 as key targets. Deletion of these indicated that while TIAM1 deficiency could suppress Apc-driven hyperproliferation, it had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 76 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…The paramount role played by Rho GTPases in the invasive and migratory behavior of cancer and stromal cells within the tumor microenvironment has raised a growing interest on RhoGEFs as crucial effectors and potential therapeutic targets in metastatic cancer ( 6 , 9 , 11 , 17 , 20 , 21 , 25 , 30 , 31 , 72 , 73 , 74 , 75 , 76 ). Here, we demonstrate that ARHGEF17, component of a transcriptional signature predictive for reduced survival in various cancers ( 58 ), is involved in invasion and migration of lung cancer cells elicited by Gi-coupled LPARs.…”
Section: Discussionmentioning
confidence: 99%
“…The paramount role played by Rho GTPases in the invasive and migratory behavior of cancer and stromal cells within the tumor microenvironment has raised a growing interest on RhoGEFs as crucial effectors and potential therapeutic targets in metastatic cancer ( 6 , 9 , 11 , 17 , 20 , 21 , 25 , 30 , 31 , 72 , 73 , 74 , 75 , 76 ). Here, we demonstrate that ARHGEF17, component of a transcriptional signature predictive for reduced survival in various cancers ( 58 ), is involved in invasion and migration of lung cancer cells elicited by Gi-coupled LPARs.…”
Section: Discussionmentioning
confidence: 99%
“…As the first specific Rac1 inhibitor, NSC23766 targets Rac1 activation through GEFs (Trio or Tiam1) but does not interfere with the binding or activation of the closely related targets Cdc42 or RhoA (168,169). The seven residues on Rac1 are very important for the interaction of NSC23766 and Tiam1 (170).…”
Section: General Rac1 Inhibitormentioning
confidence: 99%
“…Interactome analysis revealed a significant association of Rac1 with Zol activity, which was previously shown to be associated with RR in PDAC ( Figure 4 c ). 27 , 28 , 29
Figure 4 Zol and RT treatment modulate DNA damage response by deactivating Rho small GTPases, thereby reducing DNA double-stranded break repair proteins. (a) Venn diagram showing specific differentially expressed genes in different treatment groups.
…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Rac1 was shown to be overexpressed and constitutively activated, and its activity was unaffected by anticancer agents. 28 29 33 34 . However, we found that Rac1, associated with PDAC RR, was downregulated and among the network genes affected with Zol+Rad treatment.…”
Section: Discussionmentioning
confidence: 99%